Peran Mediator Hubungan Industrial Dalam Menyelesaikan Perselisihan Hubungan Industrial Pada Dinas Tenaga Kerja, Koperasi Usaha Kecil dan Menengah Kota Madiun - Genies Wisnu Pradana; Purwono Sungkowo Raharjo (Jurnal Discretie, 2022)
This study aims to determine and analyze the role of mediator in industrial relationship dispute settlement on Departement of Manpower, Cooperatives Small And Medium Enterprise Madiun City and obstacles factors mediator in industrial relationship dispute settlement. This research is normative legal research which is prescriptive. The research location is Department of Manpower, Cooperatives Small And Medium Enterprise Madiun City. Types of legal materials used are primary legal materials and secondary legal materials. In this research, using statute approach with literature study data collection techniques. Furthermore, using analysis techniques that are deductive. The results of the study indicate that the role of the mediator in resolving industrial relations disputes is to encourage the disputing parties to resolve industrial relations disputes by deliberation to reach an agreement, make written recommendations if there is no agreement, and notify the need for the results of the agreement. collective agreements to be registered at the Industrial Relations Court, while the obstacles to the settlement of industrial relations disputes are still employers who are not present at the mediation or are represented by those who are not authorized to make decisions, thereby hampering the settlement of industrial relations disputes. relationship disputes, there are still workers who do not know the procedure for the settlement of industrial relations in connection with the non-completion of bipartite negotiations, there are no provisions regarding the distribution of money between entrepreneurs and workers/labor, and administrative rules are not implemented.Penelitian ini bertujuan untuk mengetahui dan menganalisis tentang peran mediator dalam menyelesaikan perselisihan hubungan industrial pada Dinas Tenaga Kerja, Koperasi Usaha Kecil Dan Menengah Kota Madiun dan faktor penghambat mediator dalam menyelesaikan perselisihan hubungan industrial. Penelitian ini merupakan penelitian hukum normatif yang bersifat preskriptif. Lokasi penelitian adalah di Dinas Tenaga Kerja, Koperasi Usaha Kecil dan Menengah Kota Madiun. Jenis bahan hukum yang digunakan adalah bahan hukum primer dan sekunder. Dalam penelitian ini menggunakan pendekatan undang-undang (statute approach) dengan teknik pengumpulan data studi pustaka. Selanjutnya menggunakan teknik analisa yang bersifat deduksi. Hasil penelitian menunjukan peran mediator dalam menyelesaikan perselisihan hubungan industrial adalah medorong para pihak yang berselisih untuk menyelesaikan perselisihan hubungan industrial secara musyawarah untuk mencapai kesepakatan, membuat anjuran tertulis jika tidak terjadi kesepakatan, dan memberitahu perlunya hasil perjanjian bersama didaftarakan pada Pengadilan Hubungan Industrial, sedangkan hambatan dalam menyelesaikan perselisihan hubungan industrial adalah masih adanya pengusaha tidak menghadiri mediasi atau diwakilkan kepada yang tidak memiliki otoritas memutuskan sehingga menghambat penyelesaian perselisihan hubungan industrial, masih ada pekerja yang tidak mengetahui tatacara penyelesaian hubungan industrial kaitannya dengan tidak diselesaikan perundingan secara bipartit, belum adanya ketentuan mengenai uang pisah yang dibuat antara pengusaha dan pekerja/buruh, dan tidak dilaksanakannya tertib administrasi.